Spectral characteristics of intracranial electroencephalographic activity in patients with Lennox–Gastaut syndrome - Lee, Dongpyo; Liang, Junge; Hur, Yun Jung; Kim, Nam-Young; Kim, Heung Dong (Brain & development (Tokyo. 1979), 2017)
The purpose of the current study was to characterize the frequency profiles of epileptogenic regions, independent of visible epileptiform discharges, in intracranial EEG (iEEG) recordings of Lennox–Gastaut syndrome (LGS) patients. We selected eight LGS patients who underwent resective surgery in the absence of definite neuroimaging findings. We calculated the absolute and relative band powers of continuous spike-free iEEG data and compared the characteristics of the resected and remaining regions. For absolute band powers, there was a trend for higher absolute gamma band power in the remaining brain section. We also found that the absolute delta power in the resected area was higher than that in the remaining area. However, this trend was not statistically different in all patients. For relative band powers, we found decreased relative band power in the beta and gamma band ranges within the areas defined by the surgical margins. Delta, theta, and alpha relative band power differences between the resected and remaining areas were inconsistent between the subjects. Our results showed systematic relative beta and gamma band power variation in the resected areas of LGS patients.